Incidental Discovery of Amyand's Hernia in an Adult Female: A case report - Sikakulya, Franck Katembo; Kiyaka, Sonye Magugu; Masereka, Robert; Onyai, Patrick; Anyama, Philip (International Journal of Surgery Case Reports, 2021)
Amyand's hernia is a rare type of inguinal hernia with an incidence of about 0.1% of all inguinal hernias with most in occurring in childhood. It is characterized by the presence of the vermiform appendix within the hernia sac.
Keywords: Amyand's hernia; Adult female; Hernia repair; Case report